Framework para integração semântica de dados geoespaciais: integração de dados geológicos - Antonialli, Rodrigo Cesar [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Data integration is a constant need in researches and work in Geology, part of Geosciences responsible for studying several characteristics of Earth. This need comes from the fact that data are usually produced by different organizations and/or research groups, which may study large areas and/or relate different subjects associated with Geology within these studies. The decentralized information production cause the data to be described with different schemas and different interpretations of the concepts related to them. The volume of data that can be generated in Geological studies brings the need to automate the integration process. However, traditional approaches based on syntactic comparison of data schema may not be enough to perform the task. Geological data have complex characteristics which rely on conceptual aspects to be analyzed. Thus, geological data integration a more complete level of information representation approach, that considers the concepts related to the data. Within the presented context, the Framework for Geospatial Semantic Integration proposed in this work aims to integrate geological data based on ontologies, and to consider the fundamental geospatial characteristics of these data. However, the ontologies that describe concepts related to Geology may be defined with different interpretations of these concepts relations. To overcome this semantic heterogeneity, the proposed framework uses the ontology alignment process. The framework also considers geological data availability aspects, which may vary as public, with free access and sharing possibilities or as restricted, with controlled access, mainly when the data is about strategic activities, as mineral and energetic resources exploration. In the integration process proposed in the framework, a semantic analysis of the data is executed; based on rules, it identifies cases of duplications, conflicts or combinations of geological data

A necessidade de integrar dados é constante nos estudos e trabalhos na área de Geologia, parte das Geociências responsável pelo estudo de diversas características da Terra. Esta necessidade surge do fato de que os dados são, geralmente, produzidos por diferentes organizações e/ou grupos de pesquisas, que podem estudar áreas extensas e/ou relacionarem, nestes estudos, diferentes disciplinas associadas à Geologia. Esta descentralização na produção de informação faz com que os dados sejam descritos com diferentes esquemas e diferentes interpretações de conceitos a eles relacionados. O volume de dados que pode ser gerado nos estudos de Geologia traz a necessidade de automatizar processo de integração. Entretanto, abordagens tradicionais baseadas em comparações sintáticas dos esquemas de dados podem não ser suficientes. Os dados geológicos possuem características complexas que dependem de aspectos conceituais para serem analisados. Portanto, a integração de dados geológicos requer uma abordagem em um nível mais completo de representação da informação, que considere os conceitos relacionados aos dados. A partir do contexto apresentado, o Framework para Integração de Dados Geoespaciais proposto neste trabalho visa integrar dados geológicos com a utilização de ontologias, considerando como escopo fundamental as características geoespacias destes dados. Porém, as ontologias que descrevem conceitos relacionados à Geologia podem ser definidas com diferentes interpretações da relação entre estes conceitos. Para superar esta heterogeneidade semântica, o framework proposto utiliza o processo de alinhamento de ontologias. O framework também aborda aspectos relacionados à disponibilidade dos dados geológicos, que podem ser públicos, de livre acesso e compartilhamento ou restritos, com acesso controlado, principalmente quando dizem respeito a atividades estratégicas, como a exploração de recursos minerais...
Keywords: Computação - Matematica; Sistemas de informação geografica; Sistemas de dados espaciais; Framework (Programa de computador); Ontologias (Recuperação da informação); Integração semântica (Sistemas de computação); Algoritmos de computador; Geographic information systems